A critical appraisal of microemulsions for drug delivery: part II. (January 2014) - Sapra, Bharti; Thatai, Purva; Bhandari, Sameer; Sood, Jatin; Jindal, Manish; Tiwary, Ashok K
Microemulsions are thermodynamically stable, optically transparent isotropic solutions of oil and water successfully formulated by using a combination of suitable surfactant and cosurfactant. The solubilization power of microemulsions for lipophilic, hydrophilic and amphiphilic solutes form a viable approach for enhancing the bioavailability of hydrophobic drugs and percutaneous permeation of poorly permeable drugs, mainly due to the large area per volume ratio available for mass transfer. Microemulsions have emerged as novel vehicles for drug delivery due to their versatile applications. They allow sustained release for topical, oral, nasal, intravenous, ocular, parenteral and other administration routes of drugs. They also offer a relevant application platform for improving target specificity, therapeutic activity, and reducing toxicity of drugs.